A study on upper extremity musculoskeletal discomfort related to computer use among university students - Fazita, Abdul Talib (2013)
A limited number of studies have focused on computer-use-related upper extremity musculoskeletal discomfort among college students, though risk factors in terms of exposure may be similar to professional workers who use computers. The use of computer has increased among college students, as have musculoskeletal symptoms. There is evidence that these symptoms can be reduced through ergonomics and education approach. From literature reviews, it was found that the following were risks factors related to computer use: body posture, duration of computer use, psychosocial factors, work environment, complaints and history of musculoskeletal problems. In this study, the associations of these independent variables to upper extremity musculoskeletal discomfort (dependent variable) among college students were determined. In other words, the purpose of this study was to examine whether the risk factors for upper extremity musculoskeletal discomfort among college students would significantly lead to musculoskeletal discomfort especially upper extremity musculoskeletal discomfort. A cross-sectional correlation study was carried out to determine the correlation. A total of 132 questionnaires were distributed, only 130 (98.5%) students completed a self-administered questionnaire concerning the risk factors and the upper extremity musculoskeletal discomfort specifically associated with computer use. The research hypotheses were tested using Pearson Correlation Analysis. The results revealed that body posture, psychosocial factors, complaints and history of musculoskeletal pain were significantly correlated to upper extremity musculoskeletal discomfort. However, duration of break time and work environment were on the contrary. Multiple Regression results revealed that 35.8% of the variance (R-square) in upper extremity discomfort has been significantly explained by the six independent variables. There were other factors that need to be considered that might contribute to upper extremity musculoskeletal discomfort. The findings signal a need for intervention, apart from ergonomics parameters various psychosocial workplace factors need to be considered while designing a preventive intervention program, including training and education on posture, prior to entry into the workforce. Students are future workers therefore it is important to determine whether their increasing exposure to computers, prior to entering the workforce may make them already injured or do not enter their chosen profession due to upper extremity musculoskeletal discomfort. The future health of undergraduate students deserves consideration, therefore more research is needed on this matter